KINETICS OF THE MASS TRANSFER OF OXYGEN FROM AIR BUBBLES IN THE PROCESSES OF YEAST BІOSYNTHESIS - Ivanitsky, G.; Obodovich, A.; Sidorenko, V. (Energy and Automation, 2016)
The analytical study  has been carried out to throw light on the kinetics of oxygen absorption from air bubbles in a culture medium in the process of cultured of the yeast biomass in the bubble-type  fermenters. The quantitative dependences of both the surface and volumetric mass transfer coefficients on the average diameter of the gas bubbles have been determined.